Analisis Kovariansi pada Rancangan Acak Lengkap dengan Peubah Pengiring Berganda Menggunakan Pendekatan Matriks - Wimmi Sartika; Lutfian Almash; Yenni Kurniawati (Journal of Mathematics UNP, 2014)
Abstract ––  The analysis of covariance is a statistical analysis  that combine the analysis of variance and regression analysis. Analysis of covariance is another technique of analysis that is used for improving the precision of an experiment. Suppose that in an experiment with a respon  variable  there is another variable, say covariate . This variable X can’t be controlled by experiment and linearly with  variable  . The purpose of this research to explaine the source of variation from analysis of covariance in design random complete with multiple covariates use matrix. For analyzing this research, that is analyzed sum squares and products for each source of variations. The result of this research , the source of variations contain error, total, and treatment. There is influence of regression that explaine covariates. Thus, this research also include hypothesis testing to know there is  influence of treatment with respons. Keywords –– Matrix, design random complete, regression analysis, covariate variable,  and analysis of covariance.